2005
DOI: 10.1007/s10722-005-2257-x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Weedy Rice Grown in Bhutan and the Force of Genetic Diversity

Abstract: In Bhutan, weedy rice (Oryza sativa L.) was grown together with cultivated rice on terraced paddy fields lower than 2620 m above sea level. Seeds of cultivars and weedy strains were collected at 22 collection sites located from 1000 to 2620 m above sea level. Cultivars with round seeds were frequently found in fields higher than 2250 m, and those with slender seeds in fields lower than 1630 m. All cultivars and weedy strains were divided into indica or japonica types by isozyme (multi-locus) and morpho-physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 15 publications
2
47
1
1
Order By: Relevance
“…Phylogenetic and demographic analysis based on whole-genome sequencing revealed that Chinese weedy rice was de-domesticated independently from the cultivated rice, standing variations and new mutations contributed differently to the rapid adaptation of japonica and indica type of weedy rice from four representative regions of China (Qiu et al 2017). Similar results were found for the origins of weedy rice in Thailand and Bhutan (Prathepha 2009;Ishikawa et al 2005). Notably, crossing experiments involving intersub-specific and inter-varietal hybridization have generated progenies that exhibit weedy rice traits.…”
Section: Origin and Evolutionsupporting
confidence: 57%
See 1 more Smart Citation
“…Phylogenetic and demographic analysis based on whole-genome sequencing revealed that Chinese weedy rice was de-domesticated independently from the cultivated rice, standing variations and new mutations contributed differently to the rapid adaptation of japonica and indica type of weedy rice from four representative regions of China (Qiu et al 2017). Similar results were found for the origins of weedy rice in Thailand and Bhutan (Prathepha 2009;Ishikawa et al 2005). Notably, crossing experiments involving intersub-specific and inter-varietal hybridization have generated progenies that exhibit weedy rice traits.…”
Section: Origin and Evolutionsupporting
confidence: 57%
“…According to De-Wet and Harlan (1975), weedy rice originated from the selection and adaptation of wild rice to agricultural habitats. In regions where no wild rice has been grown, weedy rice may instead originate from cultivated rice through de-domestication with adaptive mutations and the accumulation of beneficial mutants (Ishikawa et al 2005;Cao et al 2006;Reagon et al 2011;Thurber et al 2010;He et al 2014;Qiu et al 2014;Lu et al 2016;Li et al 2017;Qiu et al 2017). In the case of Brazil and Italy, where no wild Oryza types are indigenous, contamination of seed stocks with wild Oryza species has been proposed as a source of weedy rice (Carney 2004;Grimm 2014).…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…Beyond the United States, genetic and morphological data for weedy rice populations in some other parts of the world also suggest a de-domesticated origin, including weed strains in China (Cao et al, 2006), Japan (Akasaka et al, 2009) and Bhutan (Ishikawa et al, 2005). There is also evidence that not all weedy rice populations are necessarily descended directly from cultivated ancestors.…”
Section: Hybrid To Weedmentioning
confidence: 99%
“…PCR conditions were the same as above except for 52掳C for annealing temperature. Genotypes were scored using the silver staining method described in Ishikawa et al (2005).…”
Section: Analysis For Ssrs Flanking Acp1mentioning
confidence: 99%